Coverage of Japan's Tsunami Included Few Social Media Sources. (September 2014) - Fontenot, Maria; Luther, Catherine A.; Coman, Ioana
Comparison of sources used by four major U.S. and Japanese newspapers that covered Japan's tsunami finds each nation's newspapers relied equally on non-official and official sources. However, few sources came from social media outlets.